The Default Risk of Swaps - COOPER, IAN A.; MELLO, ANTONIO S. (Journal of Finance, 1991)
ABSTRACT We characterize the exchange of financial claims from risky swaps. These transfers are among three groups: shareholders, debtholders, and the swap counterparty. From this analysis we derive equilibrium swap rates and relate them to debt market spreads. We then show that equilibrium swaps in perfect markets transfer wealth from shareholders to debtholders. In a simplified case, we obtain closed‐form solutions for the value of the default risk in the swap. For interest‐rate swaps, we obtain numerical solutions for the equilibrium swap rate, including default risk. We compare these with equilibrium debt market default risk spreads.